The arctic incident ebook - Colfer, Eoin (Artemis Fowl, 2009)
Artemis is at boarding school in Ireland when he suddenly receives an urgent video-email from Russia. In it is a plea from a man who has been kidnapped by the Russian Mafiya: his father. As Artemis rushes to the rescue, he is stopped by captain Holly Short of the LEPrecon fairy police. But this time, instead of battling the fairies, he is going to have to join forces with them if he wants to save one of the few people in the world he loves.